The Latin Deli : Prose and Poetry - Cofer, Judith Ortiz, 1952- (UPCC book collection on Project MUSE., 1993)
Prose and poetry of a particular immigrant experience and also of such universal themes as the pains, confusions, and wonders of growing up.